Awareness of Health Consequences of Extra Marital Relationship among Couples in Umuahia South LGA of Abia State, Nigeria - V. O., Ezebuiro; M.O. , Kalu; B.O, Ibe (Journal of Home Economics Research, 2024)
The study investigated the awareness of health consequences of extra- marital relationship among couples in Umuahia South Local Government Area, Abia State, Nigeria. Three objectives and three research questions guided the study. Descriptive survey design was adopted for the study. The population consisted of 55,428 couples in the 10 communities of Umuahia South LGA. A random sample of 500 respondents was drawn for the study. The instruments for data collection were questionnaire and focus group discussion guide. Data were analyzed using means for quantitative data while the qualitative data was used to substantiate the quantitative data. The findings revealed that married couples are aware of the physical, emotional and social health consequences of extra marital relationship. It was therefore, recommended among others, that marital counseling services that stresses the importance of marriage, marriage enrichment and marital commitment be made available to the couples.